Acquired ALK G1202R-, ALK I1171N-, or EML4-ALK-mediated resistance to ensartinib in lung adenocarcinoma but responded to lorlatinib: A case report - Ye, Zhifeng; Guo, Junhua (Frontiers in Oncology, 2023)
ALK rearrangements are identified as driver mutations in non-small-cell lung cancer (NSCLC). EML4 is the most common partner of ALK rearrangements. Here, we reported a patient with lung adenocarcinoma who was identified with EML4-ALK mutations when he progressed on an immune checkpoint inhibitor. The patient was treated with alectinib and obtained a progression-free survival (PFS) of 24 months. Then, next-generation sequencing on circulating tumor DNA identified multiple ALK mutations, including ALK G1202R, I1171N, ALK-ENC1, and EML4-ALK. Ensartinib was given, and the patient achieved a PFS of 5 months. After progression, lorlatinib was administered, and the patient achieved a partial response. Now, the benefit is still ongoing with a PFS over 10 months. Our case may provide evidence for the treatment choice of multiple ALK mutations, including ALK I1171N.